Ampelomyces strains isolated from diverse powdery mildew hosts in Japan: Their phylogeny and mycoparasitic activity, including timing and quantifying mycoparasitism of Pseudoidium neolycopersici on tomato. - Márk Z Németh (Public Library of Science (PLoS), 2021)
A total of 26 Ampelomyces strains were isolated from mycelia of six different powdery mildew species that naturally infected their host plants in Japan. These were characterized based on morphological characteristics and sequences of ribosomal DNA internal transcribed spacer (rDNA-ITS) regions and actin gene (ACT) fragments. Collected strains represented six different genotypes and were accommodated in three different clades of the genus Ampelomyces. Morphology of the strains agreed with that of other Ampelomyces strains, but none of the examined characters were associated with any groups identified in the genetic analysis. Five powdery mildew species were inoculated with eight selected Ampelomyces strains to study their mycoparasitic activity. In the inoculation experiments, all Ampelomyces strains successfully infected all tested powdery mildew species, and showed no significant differences in their mycoparasitic activity as determined by the number of Ampelomyces pycnidia developed in powdery mildew colonies. The mycoparasitic interaction between the eight selected Ampelomyces strains and the tomato powdery mildew fungus (Pseudoidium neolycopersici strain KTP-03) was studied experimentally in the laboratory using digital microscopic technologies. It was documented that the spores of the mycoparasites germinated on tomato leaves and their hyphae penetrated the hyphae of Ps. neolycopersici. Ampelomyces hyphae continued their growth internally, which initiated the atrophy of the powdery mildew conidiophores 5 days post inoculation (dpi); caused atrophy 6 dpi; and complete collapse of the parasitized conidiphores 7 dpi. Ampelomyces strains produced new intracellular pycnidia in Ps. neolycopersici conidiophores ca. 8-10 dpi, when Ps. neolycopersici hyphae were successfully destroyed by the mycoparasitic strain. Mature pycnidia released spores ca. 10-14 dpi, which became the sources of subsequent infections of the intact powdery mildew hyphae. Mature pycnidia contained each ca. 200 to 1,500 spores depending on the mycohost species and Ampelomyces strain. This is the first detailed analysis of Ampelomyces strains isolated in Japan, and the first timing and quantification of mycoparasitism of Ps. neolycopersici on tomato by phylogenetically diverse Ampelomyces strains using digital microscopic technologies. The developed model system is useful for future biocontrol and ecological studies on Ampelomyces mycoparasites.